Black corals (Cnidaria: Anthozoa: Antipatharia): first records and a new species from the Brazilian coast - Echeverría, Carlos Alejandro (2002)
A new species, C irripathes secchini (Cnidaria: Antipatharia) from the Abrolhos area (Bahia, Brazil) is described and constitutes the first record to this genus from Brazil. Two other species ( Antipathes hirta, first record from the Southwestern Atlantic; and Antipathes fernandezi, first record from the Atlantic Ocean) are compared to the most recent redescriptions and new data on the size distribution of the characters is provided. To the present there are only two records of the order Antipatharia from Brazil